Investigation of Career Interest in the Tax Field for Tax Voluntary Students in the Banten Province - Umi Faridah; Ibrohim Ibrohim; Mochamad Fahru Komarudin (International Journal of Economics, Commerce, and Management, 2024)
This research to investigate empirical of tax knowledge, self-efficacy, gender on career desire in the field of tax for Tax Volunteer Students in Banten Province. This study uses a quantitative method (questionnaire). As much as 654 Tax Voluntary Students with a sample of 167 VoluntarY- Sample collection method was using the convenience sampling technique. The information examination utilized could be linear regression test. The speculation testing in this consider appear that knowledge of taxation and gender have an effect on career desire in taxation for tax voluntary students in Banten province, while self-efficacy no effect on career desire in tax for tax voluntary students in Banten province. Based on this research, tax knowledge and gender socialization need to be improved for students because in addition to high tax knowledge, gender equality in the world of work can also increase career desire in the tax field for tax voluntary students in the Banten province.